The complex associations between scientific reasoning and advanced theory of mind. Issue 1 (2nd November 2022) - Osterhaus, Christopher; Koerber, Susanne
Abstract: This 6‐wave longitudinal study (2014–2018) of 161 German 5‐ to 10‐year‐olds from a midsized city and rural area in southern Germany (89 females, 72 males; predominantly White; mostly middle class) found that scientific‐reasoning abilities first develop at 6 years. Abilities were highly stable, with the kindergarten score predicting 25% of end‐of‐elementary‐school variance. Individual but not developmental differences were related to language abilities (0.39), mindreading skills (0.33), and parental education (0.36). In early elementary school, mindreading skills predicted scientific reasoning (0.15), but not vice versa; in late elementary school, bidirectional associations emerged (0.11–0.33). Our findings suggest that mindreading is a precursor for the development of scientific reasoning and that older children use scientific reasoning to revise their advanced theories of mind.